2019
DOI: 10.1007/s11575-019-00399-2
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Reshoring Sentiment and Animosity: Expanding Our Understanding of Market Responses to Reshoring

Abstract: Although an increasing body of research has focused attention on reshoring, namely, a company's decision to relocate activities back to the home-country, how and when reshoring impacts market responses remains largely understudied and requires specific theoretical and empirical consideration. Our study complements existing research on reshoring by adopting a demand-side perspective. Through multiple, experimental and survey-based studies, conducted in two countries (Italy and the US), we verified that the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 52 publications
1
28
1
Order By: Relevance
“…Di Di Mauro et al, 2018;Gray et al, 2013;Tate et al, 2014), the consumer's viewpoint remains under-researched (Ashby, 2016;Fratocchi and Di Stefano, 2019;Moretto, Patrucco and Harland, 2020;Srai and Ané, 2016). This is surprising, because the literature affirms that consumers are increasingly demanding authentically and locally made products, and are willing to pay more for them (Collins and Weiss, 2015;Grappi, Romani and Bagozzi, 2020;Robinson and Hsieh, 2016). In a seminal study examining consumers' willingness to buy products from companies that reshore, Grappi, Romani and Bagozzi (2015) found that a company's reshoring decision positively influenced consumer attitudes towards the organisation through increased gratitude and decreased anger.…”
Section: Reshoring and Consumer Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Di Di Mauro et al, 2018;Gray et al, 2013;Tate et al, 2014), the consumer's viewpoint remains under-researched (Ashby, 2016;Fratocchi and Di Stefano, 2019;Moretto, Patrucco and Harland, 2020;Srai and Ané, 2016). This is surprising, because the literature affirms that consumers are increasingly demanding authentically and locally made products, and are willing to pay more for them (Collins and Weiss, 2015;Grappi, Romani and Bagozzi, 2020;Robinson and Hsieh, 2016). In a seminal study examining consumers' willingness to buy products from companies that reshore, Grappi, Romani and Bagozzi (2015) found that a company's reshoring decision positively influenced consumer attitudes towards the organisation through increased gratitude and decreased anger.…”
Section: Reshoring and Consumer Behaviourmentioning
confidence: 99%
“…Most reshoring literature has examined the effects of reshoring on supply chains and operations management (Gray et al, 2017;McIvor and Bals, 2021;Wiesmann et al, 2017), as well as the motivators, outcomes, and barriers to reshoring (Ellram, Tate and Petersen, 2013;Fratocchi and Di Stefano, 2019). However, research from the consumer's perspective (see Grappi, Romani and Bagozzi, 2015, 2020Pal, Harper and Vellesalu, 2018) is limited (Fratocchi and Di Stefano, 2019;Grappi, Romani and Bagozzi, 2020), despite the potential effect of consumer brand perceptions on reshoring decisions (Eurofound, 2019). In a recent Deloitte study, one of the few exploring the consumer perspective, around 65% of consumersindividual and corporate -preferred locally manufactured products and organisations with operationally excellent supply chains and ecologically friendly approaches (Deloitte Insights, 2021).…”
Section: Introductionmentioning
confidence: 99%
“… Macroeconomics Dynamics 2019 Sayem, A., Feldmann A., Ortega-Mier, M. BRQ Business Research Quarterly X 2019 Sirilertsuwan, P., Hjelmgren, D., Ekwall, D. Journal of Fashion Marketing and Management 2019 Thakur-Werns, P. Journal of Global Operations and Strategic Sourcing 2019a Wan, L. Orzes, G., Sartor, M., Di Mauro, C., Nassimbeni, G. Journal of Purchasing and Supply Management X 2019b Wan, L. Orzes, G., Sartor, M., Nassimbeni, G. Journal of Purchasing and Supply Management X 2020 Barbieri, P., Boffelli, A., Elia, S., Fratocchi, L., Kalchschmidt, M., Samson, D. Operations Management Research 2020 Boffelli, A., Golini, R., Orzes, G., Dotti, S. Journal of Purchasing and Supply Management 2020 Boffelli, A., Johansson, M. Operations Management Research 2020 Butollo, F. Competition and Change 2020 Cassia, F. TQM Journal 2020 Gharleghi, B., Jahanshahai, A.A., Thoene, T.T. International Journal of Business and Globalisation 2020 Grappi, S., Romani, S., Bagozzi, R.P. Management International Review 2020 Gurvich, V.J., Hussain, A.S. AAPS PharmaSciTech …”
Section: Appendixmentioning
confidence: 99%
“…Using this scale, authors tested consumers' willingness to reward reshoring companies. Demand-side perspective emphasizes value creation for consumers, which differs from the firm-side point of view generally adopted by researches analyzing reshoring drivers and motivations [Grappi et al, 2018;Grappi et al 2020].…”
Section: Reshoring Driversmentioning
confidence: 99%